High-dimensional one-shot optical field compressive sensing of structured light - Yaodan Hu; Ting Men; Mingdong Yan; Weiqi Tang; Haocheng Tang; Kuanjun Fan; Zhengyan Li (Nature Communications)
Abstract Light detection, no matter with human eyes or photodetectors, has long been limited by the dimensions of the obtained information. The term dimension refers to not only the three-dimensional space and the one-dimensional time but also physical quantities completely defining a light field such as amplitude, phase, polarization, and wavelength. Conventional light detections mainly capture two-dimensional transverse spatial intensity (amplitude), sometimes color or wavelength resolved, and great efforts have been taken to expand the optical sensing dimensions. As various types of novel structured light are enabled by advanced optical field manipulation approaches, full-dimensional optical sensing of arbitrary light fields is highly demanded, to resolve three-dimensional spatiotemporal amplitude, phase, polarization, and wavelength information. Here we have proved the concept of high-dimensional one-shot optical field compressive sensing, resolving full-dimensional information of any light field. Besides ordinary light fields with spatiotemporally uniform polarization states, full-dimensional metrologies of complicated structured light are conducted, including optical vortices, radially and azimuthally polarized beams, polarization-gating fields. It is believed that this light detection framework can not only be further compactly implemented for high-dimensional one-shot light detectors, but also observe dynamic physical processes in real-time.